Die Säkularisierung des Exodus Zur Narration von politischer Emanzipation bei Sigmund Freud, Thomas Mann, Michael Walzer und Paolo Virno - Mackowitz, Laurin (Edition Moderne Postmoderne, 2019)
The cultural philosophical analysis of the secularization of the exodus contrasts despotic and emancipatory aspects of psychoanalytic, literary and political adaptations of the biblical myth.